Reflections on Disability, Justice and Abolition - Lamble, Sarah (feminists@law, 2023)
This piece offers reflections on Liat Ben-Moshe’s recent book Decarcerating Disability: Deinstitutionalization and Prison Abolition and Linda Steele’s recent book Disability, Criminal Justice and Law: Reconsidering Court Diversion and their contributions to abolitionist work, disability justice and decarceration.